Preserving third year medical students' empathy and enhancing self-reflection using small group "virtual hangout" technology. (June 2015) - Duke, Pamela; Grosseman, Suely; Novack, Dennis H.; Rosenzweig, Steven
Abstract: Background : Medical student professionalism education is challenging in scope, purpose, and delivery, particularly in the clinical years when students in large universities are dispersed across multiple clinical sites. We initiated a faculty-facilitated, peer small group course for our third year students, creating virtual classrooms using social networking and online learning management system technologies. The course emphasized narrative self-reflection, group inquiry, and peer support. Methods : We conducted this study to analyze the effects of a professionalism course on third year medical students' empathy and self-reflection (two elements of professionalism) and their perceptions about the course. Students completed the Groningen Reflection Ability Scale (GRAS) and the Jefferson Scale of Empathy (JSE) before and after the course and provided anonymous online feedback. Results : The results of the JSE before and after the course demonstrated preservation of empathy rather than its decline. In addition, there was a statistically significant increase in GRAS scores ( p  < 0.001), suggesting that the sharing of personal narratives may foster reflective ability and reflective practice among third year students. Conclusion : This study supports previous findings showing that students benefit from peer groups and discussion in a safe environment, which may include the use of a virtual group video platform.